Computational Study on the Separation of Pentane Isomers in Functionalized UiO-66 Metal-Organic Frameworks - Néstor Ariel Pérez-Chávez; Matias Rafti; Alberto Gustavo Albesa (Separations, 2025)
The efficient separation of light hydrocarbons, particularly alkanes from their isomers (C5–C6), represents a significant and energy-intensive challenge for the petrochemical industry. Metal-Organic Frameworks (MOFs) offer promising solutions due to their exceptional porosity, surface area, and, crucially, their structural and chemical tunability. This study employs advanced computational methods, including Grand Canonical Monte Carlo (GCMC) simulations and Molecular Dynamics (MD), to systematically investigate the adsorption and separation of pentane isomers (n-pentane, isopentane, and neopentane) in the UiO-66 MOF family. Specifically, the impact of organic linker functionalization with -H (parent), -NH2, -CH3, and -COOH groups on adsorption isotherms, isosteric heats, and competitive behavior in mixtures is evaluated. The analysis provides a molecular-level view of host-guest and guest-guest interactions, elucidating the recognition and selectivity mechanisms governing the separation of these C5 isomers and the potential for engineering MOF materials for this application.